Effect of natural weed and Siratro cover crop on soil fungal diversity in a banana cropping system in southwestern China - Wang, Yongfen; Zhang, Wenlong; Goodwin, Paul H.; Zheng, Si-Jun; Li, Xundong; Xu, Shengtao (Frontiers in Microbiology, 2023)
Cover crops are an important means of conservation tillage to improve soil quality. In this study, banana in Yunnan Province, China, was grown under three treatments: conventional tillage (bare soil), natural weed cover, which was primarily goosegrass (Eleusine indica (L.) Gaerth), or a cover crop of cultivated Siratro (Macroptilium atropurpureum (DC.) Urb.). Analysis of the soil fungal communities between 2017 and 2020 by Illumina Miseq high-throughput sequencing showed that most significant effects were in the intercropping area for the treatments, whereas it was rarely observed in the furrow planted with banana. Based on the Shannon and Simpson diversity indices, soil fungal diversity in the intercropping area significantly decreased following planting banana in 2017 with all three treatments. However, both the Shannon and Simpson diversity indices showed that there were significant increases in fungal soil diversity in 2019 and 2020 with natural weed cover or Siratro compared to bare soil treatment. At the end of the experiment, significant increases in fungal genera with Siratro compared to bare soil were observed with Mortierella, Acremonium, Plectophaerella, Metarhizium and Acrocalymma, and significant decreases were observed with Fusicolla, Myrothecium, Exserohilum, Micropsalliota and Nigrospora. Siratro resulted in higher stability of the soil fungal microbiome by increasing the modularity and the proportion of negative co-occurrences compared to bare soil. For fungal guilds, Siratro significantly increased saprotrophs_symbiotrophs in 2019 and 2020 and significantly decreased pathogens_saprotrophs in 2020 compared to bare soil. Using Siratro as a cover crop in the intercropping area of banana helped maintain soil fungal diversity, which would be beneficial for soil health with more symbiotrophs and less pathogens in the soil. As the study was only 3 years, however, further research is needed to determine the long-term impact of weed or Siratro cover crop on the fungal soil ecosystem and growth of banana.